Malaise in the water maze: untangling the effects of LPS and IL-1β on learning and memory - Cunningham, Colm (2008)
It has been widely described that immune activation, such as that induced by bacterial endotoxin (lipopolysaccharide, LPS) or by interleukin-1β (IL-1β) causes deficits in learning and memory. These studies have been performed in a limited number of paradigms and have often failed in their experimental design to account for features of sickness behaviour and have thus introduced potential confounding factors. As such, this literature provides an oversimplified view of the issues. A detailed reading of the literature reveals that rodents treated with LPS or IL-1β, whether systemically or centrally, do not reproducibly show clear impairments in spatial reference memory in the Morris Water Maze. Latency to find the platform is almost invariably increased, consistent with sickness and reduced locomotor speed in these animals. In studies where distance travelled or route to the platform have been examined there have been either very modest or no differences between treated groups, or stress-induced, thigmotaxic, strategies employed by the sick animals. This suggests that emotional and performance changes are more significant than cognitive impairments. There is better evidence for a deficit in contextual fear conditioning experiments induced by LPS and IL-1β and these effects are clearly dose dependent, with facilitation at low doses and impairment at higher doses. We propose that the field should be more cautious and more specific in its description of these cognitive effects and that new tasks be employed in these studies, that are not susceptible to confounding factors such as locomotor speed and elevated stress responses. Emerging data suggests that systemic insults induce more robust memory impairments in aged rodents or those with pre-exisiting neurodegenerative disease and these effects are consistent with the mild effects of infection on cognitive processes in young or healthy adults and the more severe effects, such as delirium, in the elderly and demented population.